THE HALAL STATUS OF DIGITAL GOLD AS A SHARIA INVESTMENT INSTRUMENT: A REVIEW OF FIQH MUAMALAH AND MAQASHID SHARIA - Nurdin, Nurdianasari (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
Rapid advances in financial technology have given rise to a new form of investment in the form of digital gold, which provides easier access and high efficiency, especially attractive to millennials. This study is important because it is necessary to ensure that the investment practice is in accordance with the principles of Islamic law, considering that there is still a debate about its halal. The main focus of this study is to examine the halal status of digital gold through a review of muamalah fiqh and sharia maqasid. The research was conducted with a qualitative approach through literature studies. Data sources were obtained from classical fiqh literature, DSN-MUI fatwas, OJK regulations, and relevant scientific journals. The analysis was carried out in a descriptive-qualitative manner with thematic methods, and using document triangulation techniques to ensure the validity of the data. The findings of the study show that digital gold can be considered halal if it meets the criteria of a valid contract, clear physical ownership, and is free from elements of riba, gharar, and maisir. However, many digital gold service provider platforms have not fully complied with these requirements, especially in terms of contracts and transparent proof of ownership. The lack of investor understanding and the absence of specific regulations are also the main challenges in ensuring compliance with sharia principles. This research contributes to building the relationship between fiqh muamalah and maqasid sharia. to assess the legitimacy of digital-based financial products. As a result, collective efforts are needed in ijtihad, increased transparency from service providers, and collaboration between education and regulation to build a responsive and competitive Islamic financial ecosystem in the digital era. This study advocates strengthening regulations based on sharia maqasid and encourages further research involving an empirical approach to the implementation of sharia fintech in the field